The Effect of Job Satisfaction On Sustainable Orientation: A Systematic Literature Review - Siti Handayani Maulidina; Ari Saptono; Darma Rika Swaramarinda (Universitas Persada Indonesia YAI, 2026)
This study aims to systematically examine the relationship between job satisfaction and sustainable orientation in the context of modern organizations. This literature review uses a Systematic Literature Review (SLR) approach, referring to the PRISMA guidelines. A total of 41 scientific articles published between 2020 and 2025 were qualitatively analyzed. The results of the review indicate that job satisfaction plays a significant role in shaping individual and organizational sustainability behavior. Employees who are satisfied with their jobs tend to demonstrate a higher commitment to sustainable practices, both in environmental, social, and economic aspects. Job satisfaction strengthens sustainable orientation through the mediation of organizational commitment, green HRM, and ethical climate.